Efficiency of response surface method based on central composite design in optimizing the adsorption process of cadmium metal from aqueous solutions using activated charcoal prepared from walnut shell - Esmail Mohseni; Abdolrasoul Rahmani; Zahra Hamdi; Poorya Ghorbanzadeh (Desalination and Water Treatment, 2024)
The efficiency of zinc chloride and calcium chloride for activating walnut shell charcoal as an environmentally friendly adsorbent for the removal of cadmium ions from aqueous solutions was compared. The response surface methodology (RSM) was used to optimize the laboratory parameters and the interaction between them. To study the structure and morphology of the synthesized activated carbon, FT-IR analysis and Field emission scanning electron microscopy (FE-SEM) images were used. The porosity and pores on the surface of activated carbon with the size of 20–40 nm and almost uniform distribution were observed. X-ray diffraction analysis shows that ACC has a higher crystalline structure than ACZ. TGA was used to investigate the thermal stability of activated carbon, which decomposed walnut shell charcoal between 201 and 270 °C. The maximum adsorption efficiency with R2 > 954% for activated carbon with calcium chloride (ACC) and R2 > 950% activated carbon with zinc chloride (ACZ) were obtained at pH of 9, the activated carbon dose of 125 mg/L, the cadmium concentration of 50 mg/L and the reaction time of 60 min. The results show that the efficiency of cadmium removal from wastewater using ACC is higher and this material can be used as a low cost adsorbent